2020
DOI: 10.1186/s40537-020-00346-1
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly detection optimization using big data and deep learning to reduce false-positive

Abstract: Signature-based Intrusion detection systems are not suitable anymore to be used in nowadays network environment. Because signature-based models are not able to detect new threats and unknown attacks. Due to technology improvement, the number of attacks is increasing exponentially. Statistics show that attacks number increases with a rate of 100% each year causing huge money loss, about tens of millions of dollars for ransomware attacks only. This high number of millions of new threats that are developed every … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…Hence, it is not a shock to see such a massive study in the healthcare industry (30%), followed by anomaly detection (11%), cybersecurity, data privacy & IoT (5%) and automobile and transportation (5%); (see Table A1 in Appendix). Concerning the data size, some studies indicated their data size in terms of the storage space ranging from 708 MB [72] to 600 GB [103] , while in terms of the number of observations, it ranges from 1789 [93] to 3 billion records [112] . Based on the data size (e.g., 708 MB [72] ), one can say that the study by Jallad et al [72] is not related to big data.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is not a shock to see such a massive study in the healthcare industry (30%), followed by anomaly detection (11%), cybersecurity, data privacy & IoT (5%) and automobile and transportation (5%); (see Table A1 in Appendix). Concerning the data size, some studies indicated their data size in terms of the storage space ranging from 708 MB [72] to 600 GB [103] , while in terms of the number of observations, it ranges from 1789 [93] to 3 billion records [112] . Based on the data size (e.g., 708 MB [72] ), one can say that the study by Jallad et al [72] is not related to big data.…”
Section: Methodsmentioning
confidence: 99%
“…Many anomaly detection-based research works report improved accuracy [24], [25], but the main problem with these models is their high false alarm rate [26]. Such intrusion detection models may not be able to generalize effectively on an unknown observation and may classify it as an attack even though it is an unknown benign observation [27]. Furthermore, in a dynamically changing attack scenario, an attacker finds ways to mutate the feature profile and generate attack distributions that are close to benign.…”
Section: ) Deep Learningmentioning
confidence: 99%
“…İkili sınıflandırma en iyi modelin tespiti için iyi bir metrik olarak görülen f1 skoru, duyarlılık ve kesinliğin harmonik ortalaması alınarak elde edilir [35]. Yanlış tahmin edilen pozitif örneklerin yapılan toplam negatif tahmin sayısına oranını belirten, hatalı alarm olarak da bilinen yanlış pozitif oranı, model seçimi için önemli bir metrik olup, bu oranın düşürülmesine yönelik çeşitli çalışmalar mevcuttur [36][37][38].…”
Section: Performans Metrikleriunclassified